Inclusive Growth: Requirements For Resuming the Economy and The Repercussions of the Crisis –Cas of Yemen - Bouhoreira, Abbas (Journal of Posthumanism, 2025)
The study aimed to diagnose the impact of the crisis on the Yemen economy and the requirements for Path (approach) correction to achieve inclusive growth in Yemen. It adopted the descriptive approach and the case study approach to answer the problem. The study concluded the necessity of rehabilitating institutions, continuing financial adjustment measures, protecting the poor in an urgent manner, and rebuilding fiscal space in the short term to support the economy and contain the repercussions of the crisis.